COMPOSITION ANALYSIS OF SOME SELECTED LEGUMES FOR PROTEIN ISOLATES RECOVERY - M. M. N. Qayyum; M. S. Butt; F. M. Anjum; H. Nawaz (Journal of Animal and Plant Sciences, 2012)
Four different legumes i.e. chickpea, lentil, broad and kidney beans were evaluated for chemical components, antinutritional profiling and protein isolates recovery including yield. In tested legumes, antinutritional compounds like phytates and trypsin inhibitor activities were higher in kidney bean whereas, haemagglutinin-lectin content in broad bean. However, trypsin inhibitor activity was lowest in lentil after hydration followed by cooking treatment. Proximate composition revealed that lentil contained crude protein content 31.12±1.68%, followed by chickpea (22.83±1.07%), broad bean (22.61±1.24%) and kidney beans (20.09±0.52%). The isoelectric precipitation method was used for the recovery of respective protein isolates from defatted legume samples. Lentil and chickpea showed higher protein isolates recovery, and yield as compared to other legumes. Electophoretic identification explicated that legume protein isolates polypeptide bands fall within the range of 4-70kDa. It is deduced that lentil and chickpea had better protein isolates recovery and yield thus suitable for the preparation of protein enriched food formulations.
Keywords: Legumes; Protein; Antinutritional factors; Protein isolates; SDS-PAGE.